A STUDY OF THE ATTITUDE OF CUSTOMERS AND AGENTS TOWARDS THE PROPOSED INCREASE OF FDI IN THE INSURANCE SECTOR IN CHENNAI METROPOLIS - K, Venkataramani; Kumar, R.Mohan; Brindha, G. (International Journal of Research -GRANTHAALAYAH, 2016)
This paper describes a study of the attitude of Chennai based consumers and agents towards the proposed increase in Foreign Direct Investment (FDI). The study focuses on the impact of FDI in insurance as perceived by both the customers and agents in terms of viability, service, benefits, and overall benefits vis-a-vis existing scene. A quantitative survey was conducted with a special measuring tool specifically devised for this study. The sample group consisted of Chennai based insurance customers and agents. The results indicated that the customers welcomed the increase in FDI for they perceived better and quicker service, better options, and professionalism in insurance transactions.